Problems of Formation of a Multipolar Financial System under the Centralisation of Global Capital - A. V. Kuznetsov (Мир новой экономики)
Topic. The active transnationalisation of the U.S. business after the end of the Second World War became possible thanks to the creation of the American-centric framework of the world monetary and financial system. The U. S. and the United Kingdom have become leaders in financial globalisation by monopolising global financial intermediation and creating institutional barriers to other countries’ access to international liquidity. With formal non-interference in the internal affairs of sovereign states, they made the latter dependent on the activities of informal institutions (American rating agencies, Anglo-Saxon offshore centres, Anglo-American law, etc.) that determine the rules of access of sovereign countries to world financial resources. Such a state of affairs is a significant obstacle to the establishment of a multipolar monetary and financial system.Purpose. The purpose of author’s research was the identification of the institutional features of the centralisation of global capital at the present stage of development of financial globalisation processes and identification of China’s potential, as a leader of the global economy, in creating a systemic counterweight to Anglo-Saxon domination in the global monetary and financial system.Methodology. The author based his study on a dialectical approach, the systemic, institutional approaches, and the method of comparative analysis.Results. The active inclusion of China in the global value chain has led to a complex change in the global balance of power mirrored by weakening US international influence. However, the increasing influence of China in the global economy has not yet been adequately reflected in the system of international economic and financial institutions, in which the dominant positions continue to belong to Western countries.Conclusion. The institutional reforms undertaken by the G‑20’ aimed at bringing the world economy back to the path of healthy, sustainable, balanced and inclusive growth are not quite adequate since they practically do not take into account the increased economic and financial role of the most dynamically developing countries. Such disregard for the interests and importance of developing countries (BRICS, EAEU) requires the elaboration of alternative approaches to regulating the global monetary and financial system at the regional and interregional levels.